The fight against sexually transmitted infections cannot stop in the COVID-19 era: a brazilian experience in online training for sexually transmitted infections guidelines - Gaspar, Pâmela Cristina; Santos, Adriano Santiago Dias dos; Santana, Lutigardes Bastos; Aragón, Mayra Gonçalves; Machado, Nádia Maria da Silva; López, Miguel Angel Aragón; Passos, Mauro Romero Leal; Pereira, Gerson Fernando Mendes; Miranda, Angélica Espinosa (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: The Brazilian Ministry of Health had planned face-to-face workshops for professional training about the Clinical Protocols and Therapeutic Guidelines for Comprehensive Care for People with Sexually Transmitted Infections for the year 2020. Due to the COVID-19 pandemic, the workshops were cancelled, and a new strategy was adopted: virtual meetings, called Webinars—Clinical Protocols and Therapeutic Guidelines for Comprehensive Care for People with Sexually Transmitted Infections 2020. Objective: To report the experience at the Ministry of Health in online training about the clinical protocol and therapeutic guidelines for comprehensive care for people sexually transmitted infections for health professionals in 2020. Methods: The webinars were held in partnership with the Brazilian Society of Sexually Transmitted Diseases and the Pan American Health Organization. Each chapter of the Clinical Protocols and Therapeutic Guidelines for Comprehensive Care for People with Sexually Transmitted Infections—2020 was converted into a webinar, with the participation of at least three experts, two speakers, and a moderator. Results: In total, 16 webinars were presented, covering topics such as sexually transmitted infections surveillance, prevention, diagnosis, treatment, public policies, and sexual violence. The initiative had more than 77,000 hits, with an average of 4,900 hits per webinar and the topic “syphilis” being the most accessed. The event reached all 27 federative units of Brazil, as well as 27 other countries. About 500 questions were received from the audience and answered during the sessions and/or through a document published later on by the Ministry of Health. Conclusion: Given the high number of hits and inquiries received, we can conclude that health professionals remained engaged in the topic of sexually transmitted infections during the pandemic. This experience shows the great potential of innovative methods for distance learning to promote continuing education, including a series of webinars aimed at strengthening the fight against sexually transmitted infections.